The endocannabinoid system in cancer biology: a mini-review of mechanisms and therapeutic potential - Salum, Kaio Cezar Rodrigues; Miranda, Gabriel Brendo Alves; Dias, Alessandra Lima; Carneiro, João Regis Ivar; Bozza, Patrícia Torres; da Fonseca, Ana Carolina Proença; Silva, Tamara (Oncology Reviews, 2025)
The Endocannabinoid System (ECS) plays a critical role in maintaining physiological homeostasis, influencing a range of processes such as neuroprotection, inflammation, energy metabolism, and immune responses. Comprising cannabinoid receptors (CB1 and CB2), endogenous ligands (endocannabinoids), and the enzymes responsible for their synthesis and degradation, the ECS has attracted increasing attention in cancer research. Cannabinoid receptor activation has been associated with the regulation of cancer-related processes, including cell proliferation, apoptosis, and angiogenesis, suggesting that the ECS may have a role in tumor progression and cancer treatment. Preclinical studies have shown that cannabinoids, through their interaction with CB1 and CB2 receptors, can inhibit tumor cell growth, induce programmed cell death, and suppress the formation of new blood vessels in various cancer models. Despite these encouraging findings, the clinical translation of ECS-targeted therapies remains in its early stages. The complexity of tumor heterogeneity, the variability in patient responses, and the challenges associated with the pharmacokinetics of cannabinoids are significant obstacles to the broader application of these findings in clinical settings. This review provides an overview of the current understanding of the ECS’s involvement in cancer biology, focusing on key mechanisms by which it may influence carcinogenesis. Additionally, we discuss the therapeutic potential of targeting the ECS in cancer treatment, while highlighting the limitations and uncertainties that need to be addressed through ongoing research.